SEROLOGLCAL AND PARASITOLOGICAL INVESTIGATIONS ON TOXOPLASMA INFECTION IN DOMESTEIC FOWLS IN IRAN - M.Ghorbani; M.J Gharavi (Iranian Journal of Public Health, 1990)
One hundred sixty two domestic fowls were examined for Toxoplasma infection by both indirect haemagglutination tests for Toxoplasma antibodies and inoculation of their brains intraperitoneally into mice for the parasite. The overall sero-positive rate (SPR) was 29 percent with the titers ranging from 1:20 to 1:6400. The number of each species tested and their SPR were: 74 hens (27.0%), 35 roosters (37.1%), 25 turkeys (24.0%), 12 pigeons (33.3%), 8 geese (50.0%) and 8 ducks (0.0%). Altogether 12 strains (7.4%) of T.gondii were isolated from 5 species of the birds, five strains (6.7%) from the hens, one (2.9%) from roosters, four (16.0%) from turkeys, one (8.3%) from pigeons, one (12.5%) from geese and none from the examined ducks. In one case Toxoplasma was isolated from a seronegative hen and the rest were isolated from the sero-positive fowls. All of the isolated strains were no virulent to mice. Since in Iran consumption of underdone chicken-kebab is more or less usual, Toxoplasma infections in domestic fowls any be taken into account as one of the sources of human infection.